Performance Evaluation of wastewater treatment plant of Noosh Azar company by online monitoring station - leila haddadi; reza marandi; nooshin sadjadi (Mashhad University of Medical Sciences, 2018)
Background& Objective: One of the reuses of wastewater in industries is irrigation of green space. Therefore, with proper treatment and reduction of environmental pollution of wastewater and in compliance with environmental standards, it can be used for irrigation purposes. The present study was aimed to evaluate the performance of Noosh Azar Wastewater Treatment Plant by the online monitoring station in 2016.   Materials and Methods: This descriptive cross-sectional study was performed at Noosh Azar Waste Water Treatment Plant (WWTP) in Tehran. The effluent outlet parameters include COD, BOD, TSS, TOC, Turbidity, pH and temperature which were measured 12 times/day by the online monitoring station of the refinery according to the standard methods (the Examinations of Water and Wastewater), and reported at the end of each month. Data were entered into SPSS software and analyzed using statistical indices including mean and standard deviation. Results: The average total of BOD/COD ratio in the wastewater was 0.8. The results of the study showed that the average concentration of COD, BOD and TSS of the wastewater was 1624.91 ±134.85, 1310±75.38 and 283.58± 39.76 mg/L, respectively. The average of total outlet parameters of turbidity, COD, BOD, TSS and TOC were 12.78±2.21, 83.73±12.90, 41.26±6.65, 6.70±2.14, 46.03±7.08 mg/L, and pH=7.80±0.35. The total average of removal efficiencies of COD, BOD and TSS were 93.92±3.62, 96.57±1.002 and 97.57±0.936, respectively. Conclusion: Regarding the proper performance of the activated sludge system of Noosh Azar Company, the effluent  parameters such as COD, BOD, TSS, TOC, turbidity and pH, were in accordance with the standard of the Iranian Environmental Protection Agency for irrigation use. However in order to ensure the quality of the wastewater for reuse, the microbial parameters should also be considered.